Platelet indices in stable chronic obstructive pulmonary disease - association with inflammatory markers, comorbidities and therapy - Hlapčić, Iva (Array, 2020)
Chronic obstructive pulmonary disease (COPD) is a complex inflammatory condition that can affect haemostasis. This study aimed to determine differences in platelet-related parameters between controls and COPD subjects. The hypothesis was that platelet indices are disturbed in COPD patients, and this would be accompanied by increased C-reactive protein (CRP), fibrinogen (Fbg) and white blood cells (WBC). Therefore, platelet count (Plt), platelet-related parameters – mean platelet volume (MPV), platelet distribution width (PDW), plateletcrit (Pct), their ratios (MPV/Plt, MPV/Pct, PDW/Plt, PDW/Pct), platelet to lymphocyte ratio (PLR), Plt index as well as CRP, Fbg and WBC were assessed. Materials and methods: Study included 109 patients with stable COPD and 95 control subjects, recruited at Clinical Department for Lung Diseases Jordanovac, University Hospital Centre Zagreb (Zagreb, Croatia). Complete blood count was performed on Sysmex XN-1000, CRP on Cobas c501, and Fbg on BCS XP analyser. Data were analysed with MedCalc statistical software. Results: Platelet (P = 0.007) and PLR (P = 0.006) were increased, while other platelet indices were decreased in COPD patients compared to controls. Combined model that included PLR, PDW and WBC showed great diagnostic performances, and correctly classified 75% of cases with an AUC of 0.845 (0.788 – 0.892), P <0.001. Comorbidities (cardiovascular or metabolic diseases) had no effect on investigated parameters, while inhaled corticosteroids/long-acting β2-agonists (ICS/LABA) therapy increased MPV and PDW values in COPD patients. Conclusion: Platelet indices were altered in COPD patients and they could be valuable as diagnostic markers of COPD development, especially if combined with already known inflammatory markers.